2010
DOI: 10.1289/ehp.0901232
|View full text |Cite
|
Sign up to set email alerts
|

Childhood Incident Asthma and Traffic-Related Air Pollution at Home and School

Abstract: BackgroundTraffic-related air pollution has been associated with adverse cardiorespiratory effects, including increased asthma prevalence. However, there has been little study of effects of traffic exposure at school on new-onset asthma.ObjectivesWe evaluated the relationship of new-onset asthma with traffic-related pollution near homes and schools.MethodsParent-reported physician diagnosis of new-onset asthma (n = 120) was identified during 3 years of follow-up of a cohort of 2,497 kindergarten and first-grad… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

11
342
2
5

Year Published

2012
2012
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 503 publications
(364 citation statements)
references
References 46 publications
11
342
2
5
Order By: Relevance
“…Exposure to traffic and traffic-related air pollution has been associated with adverse health, including respiratory responses such as decreased pulmonary function (Brunekreef et al 1997;Gauderman et al 2004;Sekine et al 2004;McCreanor et al 2007), increased respiratory symptoms (Bayer-Oglesby et al 2006;Vigotti et al 2007), and increased incidence of asthma or severity of asthma symptoms (Lwebuga-Mukasa et al 2004;Zmirou et al 2004;McConnell et al 2006McConnell et al , 2010, as well as with cardiovascular outcomes such as increased levels of atherosclerosis (Hoffmann et al 2007), alterations in heart rate variability (Riediker et al 2004;Schwartz et al 2005;Adar et al 2007), and increased incidence of myocardial infarction (Peters et al 2004;Lanki et al 2006;Rosenlund et al 2006;Tonne et al 2007). Toxicological evidence suggests these associations are related to both the size and composition of traffic-related particulate matter (PM) (Brook 2008;Valavanidis et al 2008;Møller et al 2010).…”
Section: Introductionmentioning
confidence: 99%
“…Exposure to traffic and traffic-related air pollution has been associated with adverse health, including respiratory responses such as decreased pulmonary function (Brunekreef et al 1997;Gauderman et al 2004;Sekine et al 2004;McCreanor et al 2007), increased respiratory symptoms (Bayer-Oglesby et al 2006;Vigotti et al 2007), and increased incidence of asthma or severity of asthma symptoms (Lwebuga-Mukasa et al 2004;Zmirou et al 2004;McConnell et al 2006McConnell et al , 2010, as well as with cardiovascular outcomes such as increased levels of atherosclerosis (Hoffmann et al 2007), alterations in heart rate variability (Riediker et al 2004;Schwartz et al 2005;Adar et al 2007), and increased incidence of myocardial infarction (Peters et al 2004;Lanki et al 2006;Rosenlund et al 2006;Tonne et al 2007). Toxicological evidence suggests these associations are related to both the size and composition of traffic-related particulate matter (PM) (Brook 2008;Valavanidis et al 2008;Møller et al 2010).…”
Section: Introductionmentioning
confidence: 99%
“…19 Socioeconomic hardships, day-to-day challenges faced by families living in poverty such as difficulties paying bills or finding work, have been proposed as potentially explanatory and alternative models or pathways through which poverty affects health. 10,20,21 Such hardships, rooted in financial strain, have also been shown to predict lower rates of smoking cessation among smokers. 22 Hardships that families face in the setting of low SES may be more easily affected by social, public health, and clinical interventions.…”
mentioning
confidence: 99%
“…On the other hand, Venn and co-workers found that the increased odds of childhood wheeze occurrence in relation to road proximity were local and only visible within 150 meters from the road. Similarly, McConnell et al (2006) and follow-up work in McConnell et al (2010) showed high risks of asthma in children residing at less than 75 meters from a major road, with susceptibility found to have significantly increased in long-term residents with no parental history of asthma. The authors also observed that these risks decreased to reach background rates at 150-200 meters from the road as illustrated in Fig .1.…”
Section: Proximity To a 'Freeway' Or A 'Major Road'mentioning
confidence: 93%
“…As this metric cannot take meteorological conditions into account, it has a limited directional dependence, and automatically assumes that all pollutants disperse in a similar manner, which is inaccurate Six out of the sixteen collected studies used this metric, either in isolation or alongside other criteria. In five of these studies, there was little evidence for an effect of major roadway proximity alone, where weak local and no associations between proximity to major roads and asthma were reported (Gauderman et al, 2005;McConnell et al, 2010). The exception of this was in the study by Gauderman et al (2005) where the residential distance from the nearest freeway was the distance investigated.…”
Section: Proximity To a 'Freeway' Or A 'Major Road'mentioning
confidence: 97%
See 1 more Smart Citation